Are older fallers different? Comparing older fallers and non-fallers in a developing country. (January 2022) - Yogi, Rachna Rebeka; Sammy, Ian; Paul, Joanne F; Nunes, Paula; Robertson, Paula; Ramcharitar Maharaj, Vidya
Objectives: Falls are common in older people, causing significant mortality and morbidity, but little is known about this phenomenon in developing countries. This study aimed to investigate falls in older people in the developing world, comparing fallers with other trauma patients. Methods: We conducted a prospective observational study of older trauma patients in Trinidad over a four-month period, comparing falls victims with other trauma patients, in relation to their demographic, pre-morbid and injury characteristics. Results: A total of 439 older trauma patients (aged ≥65 years) were included. Fallers were older (median age 75 years (interquartile range 65–89 years) vs. 70 years (interquartile range 65–79 years) in non-fallers). Overall, 65.2% of fallers were female, compared to 43.7% of non-fallers. Fallers were more likely to suffer from multiple pre-existing diseases, with 29.8% having ≥3 comordibities, compared to 9.7% of non-fallers. Fallers were also more likely to be on multiple medications: 7.1% were on five medications, compared to no non-fallers. Fallers also sustained more severe injuries and presented with higher acuity than non-fallers. Admission and referral rates were higher among fallers compared to other trauma patients (59.9% vs. 30.4%). Conclusions: Older patients who fall are a distinct group from other older trauma patients, with unique demographic, clinical and injury-related characteristics. This information is useful in planning preventive and management strategies for these patients.